Utilization of accessible resources in the fabrication of an affordable, portable, high-resolution, 3D printed, digital microscope for Philippine diagnostic applications. - Mark Kristan Espejo Cabello; Jeremie E De Guzman (Public Library of Science (PLoS), 2023)
Philippine clinical laboratory licensing requirements mandate that diagnostic microscopy for Tuberculosis (TB) sputum microscopy, urinalysis, pap smears, wet smears, an option for complete blood count, stool exams, and malaria thick and thin smears should be accessible and available in health facilities including primary care centers. However, access to these essential diagnostics is hampered by the lack of trained personnel, relatively high costs for supplies and equipment especially in rural and underserved areas. This served as motivation for our team to utilize accessible resources in the form of affordable 3D printers, available CAD software, and components to build our low-cost Openflexure microscope (OFM) prototype. We successfully fabricated our prototype for a total of 310$ with a weight of 525g. We used pathology teaching slides from the Ateneo School of Medicine and Public Health and examined the OFM prototype imaging capabilities. The calculated image resolution was 13% higher compared to an LED light microscope sample captured by a mobile phone at 40x and 15% for 100x. The sampled slide images had adequate clarity with some identifiable cellular features for Rheumatic Heart Disease (RHD), Tuberculosis in soft tissue, and Ascariasis. We were able to correct the color aberrations of the OFM we built and was able to scan images up to 1000x magnification without using oil. Given the features and cost, the OFM prototype can be an attractive and affordable option as an alternative or augmentation to diagnostic microscopy in Philippine primary care. Moreover, it may enable telepathology to support diagnostic microscopy in frontline care.